Co-localization of CD169+ macrophages and cancer cells in lymph node metastases of breast cancer patients is linked to improved prognosis and PDL1 expression. (1st January 2020) - Björk Gunnarsdottir, Frida; Auoja, Nathalie; Bendahl, Pär-Ola; Rydén, Lisa; Fernö, Mårten; Leandersson, Karin
ABSTRACT: Breast cancer is the most common form of cancer in women worldwide. Although the survival among breast cancer patients has improved, there is still a large group of patients with dismal prognosis. One of the most important prognostic factors for poor prognosis is lymph node metastasis. Increasing knowledge concerning the lymph nodes of breast cancer patients indicates that they are affected by the primary tumor. In this study we show that presence of CD169 + subcapsular sinus macrophages in contact with lymph node metastases in breast cancer patients, is related to better prognosis after adjuvant tamoxifen treatment, but only in patients with PDL1 + primary tumors. This is in contrast to the prognostic effect of CD169 + primary tumor-associated macrophages (TAMs). We further show that CD169 + macrophages were spatially associated with expression of PDL1 on nearby cells, both in primary tumors and metastatic lymph node, although PDL1 expression in metastatic lymph node as such did not have further prognostic impact. Our data suggest that CD169 + resident lymph node macrophages have a unique function in targeting immune responses against breast cancer and should be further investigated in detail.